Global security, safety and sustainability : tomorrow's challenges of cyber security : 10th International Conference, ICGS3 2015, London, UK, September 15-17, 2015. Proceedings /: tomorrow's challenges of cyber security : 10th International Conference, ICGS3 2015, London, UK, September 15-17, 2015. Proceedings. (2015) - Unknown
No abstract available